Urinary bisphenol A and S are associated with diminished ovarian reserve in women from an infertility clinic in Northern China - Ningxin Zhang; Yannan Zhao; Lingling Zhai; Yinglong Bai; Lihong Jia (Ecotoxicology and Environmental Safety, 2023)
Bisphenol A (BPA) has been demonstrated to cause ovarian toxicity including disruption of steroidogenesis and inhibition of follicle growth. Still, human evidence is lacking on its analogs such as bisphenol F (BPF) and bisphenol S (BPS). In this study, we aimed to investigate the associations between exposure to BPA, BPF, and BPS with ovarian reserve in women of childbearing age. We recruited 111 women from an infertility clinic in Shenyang, North China between September 2020 and February 2021. Anti-müllerian hormone (AMH), follicle-stimulating hormone (FSH), and estradiol (E2) were measured as indicators of ovarian reserve. Urinary BPA, BPF, and BPS concentrations were quantified by ultra-high-performance liquid chromatography-triple quadruple mass spectrometry (UHPLC-MS/MS). Linear and logistic regression models were applied to assess the associations between urinary BPA, BPF, and BPS levels and indicators of ovarian reserve and DOR, respectively. Restricted cubic spline (RCS) models were further utilized to explore potential non-linear associations. Our results showed that urinary BPS concentrations were negatively associated with AMH (β = − 0.287, 95 %CI: − 0.505, − 0.070, P = 0.010) and this inverse relationship was further confirmed in the RCS model. In addition, higher levels of BPA and BPS exposure were associated with increased DOR risk (BPA: OR = 7.112, 95 %CI: 1.247, 40.588, P = 0.027; BPS: OR = 6.851, 95 %CI: 1.241, 37.818, P = 0.027). No significant associations of BPF exposure with ovarian reserve. Our findings implied that higher BPA and BPS exposure may be related to decreased ovarian reserve.